ANALISIS PENGARUH CUSTOMER EXPERIENCE TERHADAP MINAT BELI ULANG (Studi Kasus pada Konsumen restoran The House of Raminten Yogyakarta) - Pratama Kusumawati, Ika; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2013)
The success of a restaurant can be seen from the amount of visitors who acquired continuously. But in 2012 visitors the House of Raminten restaurant has decreased and received some complaints that indicate the visitors consumer dissatisfaction, consumers who dissatisfied then do not have repurchase intention. So this research is aimed to analyze the affect of customer experience that is sense (X1), feeling (X2), thinking (X3), action (X4), and relation (X5) experience. toward the repurchase intention (Y) at The House of Raminten restaurant Yogyakarta.Data analysis uses quantitative method by IBM SPSS statistics software version 20. The population of this research are the consumers of The House of Raminten. The amount of sampels are 100 respondens and the sampling method is accidental sampling. Data collection is done by using questionnaire. The data analyze by using multiple linear regression analysis.The t test result show that customer experience (sense,feeling,thinking,action and relation experience) have positive and significant affect to repurchase intention. The multiple linier regression result show that the most dominant affect toward repurchase intention is think experience variable. The coefficient of determination (adjusted R2) obtained for 0,948, this means 94,8% repurchase intention is influenced by sense, feeling, thinking, act, and relation experience. It mean 5,2% has influenced by other variables beyond this research.